High Density Electroencephalography in Sleep Research: Potential, Problems, Future Perspective - Lustenberger, Caroline; Huber, Reto (Frontiers in Neurology, 2012)
High density EEG (hdEEG) during sleep combines the superior temporal resolution of EEG recordings with high spatial resolution. Thus, this method allows a topographical analysis of sleep EEG activity and thereby fosters the shift from a global view of sleep to a local one. HdEEG allowed to investigate sleep rhythms in terms of their characteristic behavior (e.g. the traveling of slow waves) and in terms of their relationship to cortical functioning (e.g. consciousness and cognitive abilities). Moreover, recent studies successfully demonstrated that hdEEG can be used to study brain functioning in neurological and neuro-developmental disorders, and to evaluate therapeutic approaches. This review highlights the potential, the problems and future perspective of hdEEG in sleep research.